Split Personality In Adrienne Stoltz & Ron Bass's Novel Lucid (2012) - Palupi, Isnaini Wahyu, Dr. M. Thoyibi, M.S, Dr. Phil. Dewi Candraningrum,M.Ed (2017)
The subject of the study is a novel entitled Lucid written by Adrienne Stoltz & Ron Bass that was published on October 2nd, 2012. The method of collecting data is library research and the technique of analyzing data is descriptive analysis. Then, the writer analyzes the data of hallucination according to American Psychiatric Association. The writer draws conclusion that first, the characteristic of the Lucid Novel have dual personality, the major character are Maggie and or Sloane. Sloane is a highschooler who lives in Mystic, Connecticut, and Maggie is an actress that lives in New York. Second, Sloane and Maggie have different personality based on dual identity: dual name and different friends; dual lifesytle: different fashion and visited place; dwelling place: different of consumption and leisure time; and dual personality: different of way of talking, way of life, way of behaving, and social relation. Third, Adrienne Stoltz and Ron Bass try to share the phenomenon of split personalities as a way to remind the reader that there are split personalities. Readers need to know the characteristics of split personality disorder and can be used as a criterion of personal character to evaluation. This is due to the behavior of multiple personality that often occurs outside the individual consciousness itself.